Pengaruh Perhatian Orang Tua dan Lingkungan Sekolah Terhadap Prestasi Belajar pada Siswa Kelas Tinggi SD Negeri 01 Sepanjang Tawangmangu Tahun Ajaran 2015/2016 - NOVIANINGRUM, Novianingrum (2016)
Novianingrum / A510120068. THE INFLUENCE OF PARENTAL SUPERVISION AND ENVIRONMENT OF THE SCHOOLS TO LEARNING ACHIEVEMENTS TO THEIR STUDENTS HIGH CLASS IN SD NEGERI 01 SEPANJANG TAWANGMANGU ACADEMIC YEAR 2015 / 2016. Skripsi. The Teaching and Knowledge Education. Muhammadiyah University of Surakarta. January, 2016. Parental and the school is one of the factors affecting student learning achievements. Research aims to understand the influence of parental supervision and environment of the schools to student learning achievements high class in SD Negeri 01 Sepanjang. This study included in research descriptive quantitative with the withdrawal of conclusion through statistical analysis.Population this research is all students high class ( IV, V, VI) of SD Negeri 01 Sepanjang which is 56 students.The sample it uses sample population. Technique chief, documentation and interview.Technique analysis data using analysis of linear regression multiple, test t, the f, The coefficients determination , sr and se which was preceded by test a prerequisite analysis that is test normality and the linieritas .Based on the results of the analysis linear regression multiple obtained equation: y = 36,629 + 0,213x1 + 0,220x2 .The results of the analysis of data by the economic situation of significance 5 % obtained: (1) parental supervision impact on student learning achievements .It is based on the t be seen that tcount > ttabel , namely 2,229 > 2,005 and value significance < 0.05 namely 0,030 with contributions relatively of 50,7 % and contributions effective of 16,07 % . (2) the vicinity of the school impact on student learning achievements .It is based on the t be seen that tcount > ttabel , namely 2,183 > 2,005 and value significance < 0.05 namely 0,034 denngan contributions relatively of 49,3 % and contributions effective 15,63 % . (3) parental supervision and the vicinity of the school impact on student learning achievements .It is based on the f be seen that fcount > ftabel namely 12,302 > 3.15 and value significance < 0.05 namely 0,000 .Based on the calculation on the coefficients determination known that the impact of parental supervision and environment of the schools to student learning achievements contributed of 31.7 % and 68,3 % influenced by the other factors that aren t pursuing.